Use of Mobile Advergame as Brand Communication Tool - Abdul Adis, Azaze-Azizi (Journal of Social Transformation and Regional Development, 2020)
The new and creative marketing strategies came into existence to attract consumers towards the brand by marketing agencies. One of these innovative marketing tools is mobile advergame which is observed as an attractive marketing tactic to enhance product awareness. The present study aims to identify the use of mobile advergame as a brand communication tool in Malaysia. A total of 366 Malaysian gamers were taken into consideration as respondents of this study. A structured online based questionnaire was designed for the study and self-brand congruity measurement was adopted to measure an association between consumer’s self-image and characteristics of brand’s value among gamers. The participants were asked about their experiences related to the advertisements occurred during the game. The findings revealed a positive relationship between self-brand congruity’s brand recall, brand attitude and purchase intention, entertainment brand recall, and brand attitude. As the main purpose of mobile advergame is to enhance the brand awareness; therefore, a consistency between the product and game content should be identified by the advertising company.